2017
DOI: 10.1186/s12860-017-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

Bmp-12 activates tenogenic pathway in human adipose stem cells and affects their immunomodulatory and secretory properties

Abstract: BackgroundCell-based therapy is a treatment method in tendon injuries. Bone morphogenic protein 12 (BMP-12) possesses tenogenic activity and was proposed as a differentiating factor for stem cells directed to transplantation. However, BMPs belong to pleiotropic TGF-β superfamily and have diverse effect on cells. Therefore, the aim of this study was to determine if BMP-12 induces tenogenic differentiation of human adipose stem cells (hASCs) and how it affects other features of this population.ResultsHuman ASCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 52 publications
3
59
1
Order By: Relevance
“…The gene expression of TNMD , a well‐known late stage tenogenic marker, was also increased. The increased expression of tendon‐related genes following BMP12 treatment is in good agreement with other studies performed on MSCs from mammals including human, rat, and horse . Therefore, we postulate that there will be no appreciable differences in MSCs tenogenesis when using turkey as an animal model.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The gene expression of TNMD , a well‐known late stage tenogenic marker, was also increased. The increased expression of tendon‐related genes following BMP12 treatment is in good agreement with other studies performed on MSCs from mammals including human, rat, and horse . Therefore, we postulate that there will be no appreciable differences in MSCs tenogenesis when using turkey as an animal model.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we further investigated the tenogenesis of turkey bone marrow‐derived MSCs. BMP12 is a key growth factor involved in guiding MSCs tenogenic differentiation . Previous studies have shown BMP12 provided potent signal for equine BMSCs tenogenic commitment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in chronic tendinopathies), intensified vasculogenesis could be detrimental. 30 Unlike endometrial cells from a non-pregnant uterus, in which VEGF is simultaneously expressed with MMPs, 31 both AM-MSCs and UC-MSCs showed lower MMP-1 and MMP-13 secretion compared to AD-MSCs, and there was a statistically significant difference in MMP-8 production. The increased proteolytic enzymes levels and massive leukocyte influx during the inflammatory process results in tissue destruction.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, in some applications (i.e. in chronic tendinopathies), intensified vasculogenesis could be detrimental …”
Section: Discussionmentioning
confidence: 99%